"Donate to help combat COVID-19!" How typeface affects the effectiveness of CSR marketing?. Issue 10 (16th September 2020) - Huang, Huiling; Liu, Stephanie Q.
Abstract : Purpose: Corporate social responsibility (CSR) marketing has become ubiquitous in the hospitality industry. The purpose of this paper is to examine the effectiveness of donation appeals containing warmth-focused versus competence-focused messages in hospitality CSR marketing. Moreover, we offer an innovative visual design strategy focusing on the typeface (handwritten vs machine-written) in donation appeals to encourage consumers' donations and boost their brand loyalty. Design/methodology/approach: This research used a 2 (message framing: warmth-focused vs competence-focused) × 2 (typeface: handwritten vs machine-written) between-subjects experimental design. Findings: The findings suggest that donation appeals featuring warmth-focused messages combined with handwritten typeface and competence-focused messages combined with machine-written typeface can maximize donation intention and brand loyalty. Furthermore, results from the moderated mediation analyses indicate that brand trust is the psychological mechanism underlying these effects. Practical implications: Hospitality managers should use typeface design, which is easy and inexpensive to manipulate, to enhance the effectiveness of CSR marketing. Specifically, for donation appeals featuring warmth-focused (competence-focused) messages, the handwritten (machine-written) typeface can boost consumers' donation intention and brand loyalty. Originality/value: To the best of the authors' knowledge, this research is the first to reveal the competitive advantage of typeface design in hospitality CSR marketing. This research sheds light on the congruency effects of message framing and typeface design in donation appeals on consumers' donation intention and brand loyalty while using the contemporary context of The Coronavirus Disease 2019 to test the theory.